Internalizing Religious Values through Collective Prayer Practices in Madrasah Diniyah Learning - Biantoro, Oktio Frenki; Rozikan, Muhamad (Journal of Pesantren and Diniyah Studies, 2025)
This study stems from the problem that the tradition of communal prayer at Madrasah Diniyah is often practiced as a routine but has not been studied in detail as a mechanism for internalizing religious values encompassing spiritual and socio-cultural dimensions. The purpose of this study is to examine the forms of religious values internalized through the tradition of communal prayer in learning at Madrasah Diniyah Nurul Karim Tanjungkarang Jati Kudus and to explain the process of internalization through the stages of value transformation, value transaction, and value internalization, along with their implications. This study uses a qualitative case study design. Data were collected through participatory observation of a series of prayers (Al-Fatiha, selawat, doa pembuka hikmah, Selawat Nariyah, Selawat Asnawiyah), in-depth interviews with the head of the madrasah, ustaz/ustazah, santri, and documentation of prayer texts and activity archives. The data were analyzed thematically using triangulation and member checking. The results of the study show that communal prayer functions as an instrument of internalization that combines text, affection, and local identity, producing religious dispositions such as generosity, discipline, politeness, and consistent behavior. The process moves from understanding the meaning of manners, routine practices, and role models, to values embedded in character. The implications of the findings confirm two mutually reinforcing domains, namely spiritual implications (devotion, motivation for self-improvement, inner peace) and socio-cultural implications (student cohesion and preservation of NU traditions), thus requiring the strengthening of SOPs, the interpretation of readings, and attitude evaluation so that internalization is measurable and sustainable.